The Use of Audio Visual Media in Improving Student Learning Outcomes in Islamic Education Learning at SD Negeri 6 Bandar Baru - Nelsiani, Linda; Fauziah (DEEP LEARNING: Journal of Educational Research, 2025)
This Classroom Action Research (CAR) investigates the effectiveness of audio-visual media in improving student learning outcomes in Islamic Education, specifically focusing on the attributes of the prophets, at SD Negeri 6 Bandar Baru. Recognizing the potential of multi-sensory learning experiences to enhance student engagement and comprehension, this study implemented audio-visual media as an instructional tool. The research followed a cyclical PTK model, involving planning, action, observation, and reflection. Data on student learning outcomes was collected through pre-tests and post-tests administered before and after the implementation of audio-visual media, while student engagement was observed and documented during the learning process. The study aimed to determine whether the integration of audio-visual media could lead to a significant improvement in students' understanding and retention of the material on the attributes of the prophets, as well as foster a more conducive and engaging learning environment. The findings of this research demonstrated a positive impact of audio-visual media on student learning outcomes in Islamic Education concerning the attributes of the prophets at SD Negeri 6 Bandar Baru. A comparison of pre-test and post-test scores revealed a statistically significant improvement in students' understanding of the material. Furthermore, observations indicated increased student engagement, participation, and enthusiasm during lessons that incorporated audio-visual aids. The interactive and multi-sensory nature of the media appeared to facilitate better comprehension and retention of complex concepts. These results suggest that the strategic application of audio-visual media can be a valuable pedagogical approach for enhancing learning outcomes in Islamic Education, particularly for abstract topics like the attributes of the prophets, and warrants further exploration and implementation in similar educational settings.